Campeau's acquisition of federated - Kaplan, Steven N. (Journal of Financial Economics, 1989)
I analyze the acquisition of Federated Department Stores by Campeau Corporation and find that after the purchase the value of Federated assets increased by more than 1.8 billion. Federated and Campeau defaulted on the debt used to finance the acquisition because Campeau paid a premium of 3.4 billion for Federated, an overpayment of $1.6 billion, financed 97% of the purchase with debt, and did not have enough other assets to make up the shortfall. The Federated purchase illustrates that a highly leveraged transaction can increase value, but still not be able to make its debt payments.